Respuesta de tres tipos de sustratos en el enraizamiento de estacas y germinación de semillas de guaviduca Piper crassinervium Kunth., en la parroquia Curtincapac, cantón Portovelo. - Gutiérrez Rivera, José María (2017)
In the canton of Portovelo, province of El Oro,. Where a low and almost null natural regeneration of the guaviduca (Piper crassinervium Kunth) is evidenced, due to the adverse conditions of nature such as: rain, wind that causes the drag and loss of the seed since it does not have structures of adhesion to earth and due to its reduced size (from 1 to 2 mm). One limitation for the diffusion of the species in the peasant orchards of the Curtincápac parish, is the sexual and / or asexual propagation; as well as the management of the seedlings in their early stages of growth. Within this agricultural context and to solve this problem it was proposed at the thesis level to study the effect of different substrates for the rooting of cuttings and germination of seeds of Piper crassinervium Kunth., That allows to generate an appropriate technology for mass reproduction of the specie. From the results of the current research, it can be seen that the specie does not respond to asexual reproduction by cuttings or stakes, with none of the substrates used (bagasse, sand, mulch and agricultural soil) With the possibility that they can remain alive for about 60 days, due to their nutritive reserves but without the emission of roots, that allow to obtain a new plant. In contrast, there was positive response of the substrates in germination of seeds, from 42 and 84 days, corresponding to the highest percentage the organic mulch with 72.5% compared to sand with 40%. Keywords: Cuttings, germination, guaviduca, mulch, propagation, reproduction, rooting, substrates.